PELAKSANAAN PROGRAM TOL LAUT PT PELAYARAN NASIONAL INDONESIA - Andilas, Devi Destiani; Yanggana, Liana Angelia (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2017)
Sea Highway is one of the Indonesian governmentâs programs that aimed at reducing price disparities that occur between the West Indonesia (especially Java) and the East Indonesia with the use of sea transport. The government appointed PT Pelayaran Nasional Indonesia (PELNI) to run the Sea Highway program started from November 2015 by providing ships with the scheduled system from the western of Indonesia to the eastern of Indonesia and vice versa. This study was held to analyze the implementation of the PT PELNIâs Sea Highway program especially in aspects of routes, frequency, and volume of the transported vessel, which only restricted from Surabaya to Eastern Indonesiaâs route. The results show that the route and frequency of Sea Highway are running consistently, while the volume is increasing if itâs compare with the first time it started. The 3 aspects of Sea Highway (route, frequency, volume) influence each other; therefore itâs suggested for government to improve the efficiency of those three aspects so the Sea Highwayâs purpose in reducing price disparities in Eastern Indonesia can be achieved maximally. Moreover, the research results also show that Sea Highway program never takes the private shipping companyâs commercial route.